Influence of institutional investors on firms' corporate social performance in an emerging market - Mitra, Aditi; Abdul Latiff, Ahmed Razman; A.N., Bany-Ariffin (Inderscience Publishers, 2019)
The purpose of this paper is to investigate the link between institutional investor ownership (IIO) and corporate social performance (CSP) among firms in Malaysia. CSP Asset4 sustainability indices have been investigated in order to determine whether institutional owners reward or penalise companies for undertaking CSR activities. For this study, it is assumed that CSP Asset4 sustainability indices are suitable indicators for the performance of corporate sustainability. The results provide empirical support to the argument that institutional owners act as a promoter of CSP. This is important because the institutional investors tend to invest in emerging markets based on their perception of the firms' ability to exhibit market neutral strategies, i.e., long-term sustainable focus, communication and transparency, and size of the firm. This study contributes to the concerns of corporate management and policy-makers regarding responsible CSP related investment that may be directed towards a firm's growth and to establish competitive advantage.